Trzy pytania o kryzys ojcostwa - Gębka, Mikołaj (Wydawnictwo Naukowe UAM, 2006)
The first question is on the reason of the crisis (e.g. the crisis of fatherhood as an effect of industrialisation and urbanisation, women's emancipation movement, and armed conflicts of the 19c. and the 20c.). The second question touches upon the symptoms of the crisis (e.g. the lack of masculine models in the upbringing or the absence of the fathers). Finally, the third question deals with the crisis of fatherhood affecting only the traditional forms, or rather the whole of fatherhood as such.
Three questions of the crisis of fatherhood